Perioperative infusion of magnesium sulfate versus dexmedetomidine on the hemodynamic responses in patients undergoing laparoscopic cholecystectomy: A randomized controlled trial - Shefali Singh,; Anju R Bhalotra, (Asian Journal of Medical Sciences, 2024)
Background: Laparoscopic cholecystectomy is associated with less post-operative pain, shorter hospitalization, and a faster functional recovery as compared to the open procedure. However, like any other surgery, a stress response is induced. Anesthesia interventions such as direct laryngoscopy, tracheal intubation, and extubation involve severe sympathetic stimulation. Magnesium can block the release of catecholamines from both the adrenal gland and adrenergic nerve terminals by inhibiting of activation of membrane Ca²⁺-ATPase and Na⁺-K⁺-ATPase. Aims and Objectives: Both magnesium sulfate and dexmedetomidine decrease the release of catecholamines and attenuate pressor responses to anesthesia and surgery. Materials and Methods: Eighty-four ASA I/II patients were randomly allocated to two groups. Group D received dexmedetomidine 1 μg/kg followed by 0.4 μg/kg/h and Group M received 2 g MgSO₄ followed by 15 mg/kg/h. hemodynamic variables were recorded as T0 (after loading dose of study drug), just before (T1) and 1, 2, and 3 min after ProSeal laryngeal mask airway (PLMA) insertion (T2 [i] [ii] [iii]), before and after peritoneal insufflation (T3 and T4), before and after table tilt (T5 and T6), after resuming flat position (T7), peritoneal deflation (T8), PLMA removal (T9), and on post-anesthesia care unit admission (T10). Data were collected and analyzed using SPSS 17 statistical software. Results: The demographic profile was comparable. After the study drug administration, there was a fall in mean arterial pressure (MAP) in both groups (Group D > Group M) and no pressor response to PLMA insertion. At peritoneal insufflation, the MAP increase was significantly more in Group M at T6, T7, and T8 (31.9%, 27.9%, and 35.6% above baseline, respectively). Although there was a fall in systolic blood pressure (SBP) from the baseline throughout the procedure in both groups, SBP was significantly higher at most times in Group M as compared to Group D (P<0.05). In both groups, there was a similar rise in diastolic blood pressure after peritoneal insufflation. The mean heart rate was significantly lower in Group D at all time points. Conclusion: Dexmedetomidine seemed to be superior to MgSO₄ for ameliorating hemodynamic responses in patients undergoing laparoscopic cholecystectomy.